Taxonomic notes on Acanthopsis (Acanthaceae, tribe Acantheae): the group with semi-dense spikes and 5-fid bracts - Steyn, Hester M.; Wyk, Abraham E. Van (Phytotaxa, 2017)
Acanthopsis is a poorly understood genus taxonomically, confined to arid parts of southern Africa. The density of the inflorescences and the morphology of the bracts are taxonomically useful characters for species delimitation. This contribution focuses on the taxonomy and conservation status of those members in the genus characterized by semi-dense inflorescences with 5-fid bracts, all of which are confined to arid parts of the Northern Cape Province, South Africa. Six species, A. carduifolia, A. glabra, A. glandulopalmata, A. insueta, A. nitida and A. scullyi, are recognized in this group. Three new species, A. glandulopalmata, A. insueta and A. nitida, are described. An identification key to the species of the group with semi-dense spikes and 5-fid bracts is provided.